Effect of deferment period and cutting interval on seed yield of cv. Jacuí S2 of white clover. - Andrade, José Luiz Rocha; Nabinger, Carlos; Paim, Nilton R. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted at the Agronomic Experimental Station of UFRGS, Guaíba, RS, Southern Brazil, from May, 1987 to January, 1988. The purpose was to study forage dry mater yield, and seed production of Jacuí S2, white dover cultivar in a two-year old planting. The cultivar was submitted to two cutting intervals (four and eight weeks) and five deferment periods (end of August, September and October, and mid November and December). The deferment period from mid December, irrespective of cutting intervals, provided the lowest number of flower heads per arca, yield of seeds per flower head, seed weight, number of seeds per flower head, density and length of the stolons and seed yield per area. The eight-week cutting interval provided more forage DM yield and greater number of flowers per flower head. The deferments from early to mid spring gave the highest seed yield.